2020
DOI: 10.3390/molecules25215206
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Safflower Flavonoid Extract in 6-Hydroxydopamine-Induced Model of Parkinson’s Disease May Be Related to its Anti-Inflammatory Action

Abstract: Safflower (Carthamus tinctorius. L.), a Chinese materia medica, is widely used for the treatment of cardiovascular and cerebrovascular diseases, with flavonoids being the major active components. Multiple flavonoids in safflower bind to Parkinson’s disease (PD)-related protein DJ-1. Safflower flavonoid extract (SAFE) improved behavioral indicators in a 6-hydroxydopamine (6-OHDA)-induced rat model of PD; however, the underlying mechanisms remain unclear. We used a 6-OHDA-induced mouse model of PD and a primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 25 publications
0
12
1
2
Order By: Relevance
“…Ellagic acid (EA) harbors profound implications in protecting DA neurons by inhibiting NLRP3 inflammasome activation in the microglia [ 40 ]. Safflower flavonoid extract (SAFE) reduced the level of plasma inflammatory factors, inhibiting NLRP3 inflammasome activation in mice, exhibiting significant anti-Parkinson’s disease effects [ 41 ]. Naringin (NAR) inhibited microglial NLRP3 inflammasome signaling activation and pro-inflammatory factor release in rats and protected DA neuron viabilities in rats [ 42 ].…”
Section: Roles Of Nlrp Inflammasome In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Ellagic acid (EA) harbors profound implications in protecting DA neurons by inhibiting NLRP3 inflammasome activation in the microglia [ 40 ]. Safflower flavonoid extract (SAFE) reduced the level of plasma inflammatory factors, inhibiting NLRP3 inflammasome activation in mice, exhibiting significant anti-Parkinson’s disease effects [ 41 ]. Naringin (NAR) inhibited microglial NLRP3 inflammasome signaling activation and pro-inflammatory factor release in rats and protected DA neuron viabilities in rats [ 42 ].…”
Section: Roles Of Nlrp Inflammasome In Neuropsychiatric Disordersmentioning
confidence: 99%
“…In addition, existing evidence shows extensive NLRP3 inflammasome activation in the SN of postmortem PD brains [ 11 ]. Neurotoxins such as MPTP, 6-OHDA, and αsyn PFF can induce the activation of the NLRP3 inflammasome [ 49 51 ], and inhibiting NLRP3 inflammasomes can effectively prevent dopaminergic neurodegeneration in PD models [ 51 , 52 ]. Consistent with the above research, we detected the activation of the NLRP3 inflammasome in the SN in the MPTP model, while the administration of SR9009 effectively inhibited NLRP3 inflammasome activation and the release of the inflammatory factors IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…PINK-1/Parkin pathway is related to mitochondrial damage ( Quinn et al, 2020 ), PINK1 promoted Parkin’s mitochondrial translocation and modification, thus protecting mitochondrial DNA from damage by reactive oxygen species and stimulating the self-repair process of mitochondria ( Xu et al, 2020 ). DJ-1 is a redox sensor of oxidative stress, upregulating DJ-1 antagonize the mitochondrial dysfunction caused by PINK1 mutation, thus, DJ-1 can be used as an important indicator of mitochondrial damage ( Lei et al, 2020 ). In the present study, we found that Cannabidiol pretreatment reduced MPP + -mediated mitochondrial damage via activation of PINK-1/parkin and DJ-1.…”
Section: Discussionmentioning
confidence: 99%